Interrelations Between Transportation Development and Congestion: A Bibliometric Analysis Using VOSviewer - Agustian, Renaldi; Reta, Reci Tiana; Septiyani, Yusan Nurul; Toruan, Erni Sari Lumban; Isradi, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of transportation has become one of the important indicators of regional progress, especially amid rapid urbanization. Congestion can be defined as a condition when the transportation system does not function smoothly. This study aims to explore the relationship between transportation development and congestion through a bibliometric approach using VOSviewer. VOSviewer is a software tool designed for creating and analyzing visual maps based on bibliometric or text data. Data were collected using the Publish or Perish software, which is connected to the Google Scholar academic database, with relevant publications from 2020–2025. The collected data were then exported and analyzed using VOSviewer software to perform keyword co-occurrence analysis, network keyword on relation, co-occurrence author, and visual mapping of the research network. The highest number of year publications was in 2024, with 248 articles. the keywords “traffic congestion” and “transportation” are linked through related keywords such as smart city, machine learning, intelligent transportation system, and artificial intelligence. These keywords represent the relationship between transportation and traffic congestion. This research can also provide scientific literature in the field of transportation planning and spatial planning so that as transportation develops and grows, sustainable spatial planning can be implemented